Students' Perceptions In-Deep Learning in Science Subjects in Elementary Madrasahs - Khoirunnisa, Alifatul Fitri; Nuroniyyah, Falkha Sariirotun; Salwa, Zidny Badingatus; Fadillah, Tasya; Ngadimah, Ni’matun; Khusnaeni, Ahmad Fatkhul; Fatimah, Siti; Rinawati, Atim; Arifah, Umi (Proceeding International Conference on Religion, Science and Education, 2026)
The purpose of this study is to analyze students' perceptions of in-depth learning in the subject of science at MI Ma'arif Krakal. This study uses a descriptive quantitative approach. Respondents in this study were grade 5, 16 students. The data collection technique used a questionnaire. The data analysis technique used quantitative descriptive in the form of percentages. The results showed that 64% of students' perceptions of science lessons were classified as good.